Inhibition of p90 ribosomal S6 kinase potentiates cisplatin activity in A549 human lung adenocarcinoma cells. (15th July 2020) - Abdulrahman, Nabeel; Siveen, Kodappully Sivaraman; Joseph, Jensa Mariam; Osman, Aisha; Yalcin, Huseyin C; Hasan, Anwarul; Uddin, Shahab; Mraiche, Fatima
Abstract: Objective: Cisplatin is a standard treatment approach against lung adenocarcinoma. Resistance to cisplatin and the toxic side effects of cisplatin continue to remain a challenge. Combining drugs with different mechanisms is being investigated as a means to overcome these challenges. In ovarian cancer cells, the knockdown of RSK2 increased the sensitivity of cisplatin. RSK is a downstream mediator of the MAPK pathway that is responsible for cell survival, proliferation and migration. Methods: Our study examined the effect of cisplatin, BI-D1870 (RSK inhibitor) or their combination on cell migration, apoptosis, autophagy and cell cycle in A549 human lung adenocarcinoma cells. Key Findings: The combination of cisplatin and BI-D1870 potentiated the antimigration rate, the activation of caspases-3 and was associated with a significant decrease in RSK1 and ERK expression when compared to cisplatin alone. The combination of cisplatin and BI-D1870 also resulted in the inhibition of LC3 II to LC3 I expression when compared to BI-D1870. The combination of cisplatin and BI-D1870 increased the number of cells in the G2/M-phase when compared to cisplatin alone. Conclusions: These findings suggest that combining cisplatin with agents that target the RSK mediated cell survival pathway, may potentiate the cisplatin effect in lung adenocarcinoma.